The effect of trauma type on the severity of Post-Traumatic Stress Disorder (PTSD) symptoms - Kul, Ayşegül Taşdelen (2020)
Objective: The high prevalence of trauma exposure calls for detailed research on how trauma type affects the development of Post-Traumatic Stress Disorder (PTSD). Therefore, the aim of our study was to investigate the effects of the type of trauma on the severity of symptoms, anxiety, depression, and dissociative experiences in the PTSD patient population. Method: The sample of the study consists of 80 volunteer PTSD patients (20 sexual trauma, 20 work accidents, 20 traffic accidents and 20 combat related trauma). Once the severity of symptoms was determined in all subjects by the Clinician-Administered PTSD Scale (CAPS), Beck Depression Inventory, Beck Anxiety Inventory and Dissociative Experiences Scale (DES) were applied. Results: A statistically significant difference were found between trauma types with regard to age, time without treatment, and the total and subscale scores obtained in DES and CAPS. It was found that in the group that has PTSD diagnosis related to sexual trauma, the length of the time without treatment, DES and CAPS scores. Conclusion: The study we conducted showed that PTSD continued more severe and resistant after a sexual trauma. Moreover, specific type of trauma was significant in PTSD patients.